Muography as a new complementary tool in monitoring volcanic hazard: implications for early warning systems. (24th November 2021) - Leone, Giovanni; Tanaka, Hiroyuki K. M.; Holma, Marko; Kuusiniemi, Pasi; Varga, Dezső; Oláh, László; Presti, Domenico Lo; Gallo, Giuseppe; Monaco, Carmelo; Ferlito, Carmelo; Bonanno, Giovanni; Romeo, Giuseppe; et al.
Abstract : Muography uses muons naturally produced in the interactions between cosmic rays and atmosphere for imaging and characterization of density differences and time-sequential changes in solid (e.g. rocks) and liquid (e.g. melts ± dissolved gases) materials in scales from tens of metres to up to a few kilometres. In addition to being useful in discovering the secrets of the pyramids, ore prospecting and surveillance of nuclear sites, muography successfully images the internal structure of volcanoes. Several field campaigns have demonstrated that muography can image density changes relating to magma ascent and descent, magma flow rate, magma degassing, the shape of the magma body, an empty conduit diameter, hydrothermal activity and major fault lines. In addition, muography is applied for long-term volcano monitoring in a few selected volcanoes around the world. We propose using muography in volcano monitoring in conjunction with other existing techniques for predicting volcanic hazards. This approach can provide an early indication of a possible future eruption and potentially the first estimate of its scale by producing direct evidence of magma ascent through its conduit in real time. Knowing these issues as early as possible buy critically important time for those responsible for the local alarm and evacuation protocols.